CHANGES IN EXTRA-ARTICULAR PAIN IN PATIENTS AFTER PRIMARY HIP REPLACEMENT - I. V. Kirpichev; M. N. Kirpikova (Klinicist)
Objective: to determine the dynamics of the extra-articular pain after primary hip replacement. Materials and methods. A total of 1286 patients undergoing primary total hip arthroplasty. Among the patients were women, mean age was 56.6 ± 13.9 years. In a clinical study of patients using differential diagnostic table extra-articular pain, visual analogue scale of pain, with instrumental examination – X-ray data, and sonographic densitometry study. Results. The incidence of the disease state is 42.7 %. Risk factors for decompensation classified muscles that stabilize the hip joint (r = 0.78), shortening of the operated limb more than 3 cm (r = 0.72). The most intense pain is fixed from the 3rd to the 6th month after the surgery. The least pronounced dynamics of reduction in pain severity observed in patients with dysplastic coxarthrosis and diseases arising on a background of systemic pathology. Conclusion. Extra-articular pain occurs more than a third of patients after primary prosthesis. According to the etiology is often vertebrogenic and adaptive pain. From the 3rd to the 6th month, in connection with the formation of a new dynamic stereotype of gait is highest probability of occurrence and/or enhance the intensity of the pain, which are reduced to 12th month after surgery.